1995
DOI: 10.1590/s0074-02761995000200024
|View full text |Cite
|
Sign up to set email alerts
|

Current advances on the study of snail-snail interactions, with special emphasis on competition process

Abstract: Field work research on population dynamic of snails from the regions of Belo Horizonte and Lagoa Santa give much information about interactions among two or more species of mollusks: Pomacea haustrum, Biomphalaria glabrata, B. tenagophila, B. straminea and Melanoides tuberculata. Data ranging from two years to several decades ago suggest that the Pampulha reservoir is like a cemetery of B. glabrata and B. straminea, species that coexist for more than 14 years in a small part of a stream, whereas only B. glabra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Studies related to the interaction between M. tuberculata and some species of Biomphalaria Preston, 1910, which transmit Schistosoma mansoni Sambon, 1907 in the country have reported that endemic populations of planorbids coexists with these thiarids despite their displacement 12,13,32 . Other studies did not confirm the coexistence of planorbids with thiarids, but verified the significant decline or complete disappearance of Biomphalaria species after the introduction of thiarids 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to the interaction between M. tuberculata and some species of Biomphalaria Preston, 1910, which transmit Schistosoma mansoni Sambon, 1907 in the country have reported that endemic populations of planorbids coexists with these thiarids despite their displacement 12,13,32 . Other studies did not confirm the coexistence of planorbids with thiarids, but verified the significant decline or complete disappearance of Biomphalaria species after the introduction of thiarids 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite some studies related to the interaction between M. tuberculata and planorbid molluscs which transmit Schistosoma mansoni Sambon, 1907 in the country 13,14 , the possible damage on the native fauna as alien species and their potential to act as parasite vector in the country have not yet been evaluated. In this later aspect, some studies had already reported the finding of M. tuberculata harboring pleurolophocercous cercariae in Brazil 5,6,39 , but these larvae, characterized as Pleurolophocercous type, still remain without a specific identification.…”
mentioning
confidence: 99%
“…These values are similar to the observed in laboratory studies of M. tuberculata and B. glabrata , Giovanelli 2000. Densities of M. tuberculata in the field were always higher than densities of Biomphalaria (Pointier 1993, Freitas & Santos 1995.…”
mentioning
confidence: 79%